THE MOTHERHOOD OF THE HOLY SPIRIT - Jacob, P. J. (Journal of Dharma, 1980)
"I can only explain," wrote William Butler Yeats in 1937, "by that suggestion of recent scholars-Professor Burkitt of Cambridge commended it to my attention that St. Patrick came to Ireland not in the fifth century but towards the end of the second. The great controversies had not begun; Easter was still the first full moon after the Equinox. Upon that day the world had been created, the Ark rested upon Ararat, Moses led the Israelites out of Egypt; the umbilical cord which united Christianity to the ancient world had not yet been cut, Christ was still the half-brother of Dionysus. "An Irish-born modern poet, Yeats's Christian faith came into much discredit not only for the above remark but for several others also which could be as shocking and repulsive to any of his Christian contemporaries as to a modern Christian nurtured by the rudiments of a credulous and blind faith.